2019
DOI: 10.1111/tbj.13421
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of hypofractionated radiotherapy with concurrent anti‐HER‐2 therapy following breast‐conserving therapy for breast cancer

Abstract: The purpose of this study was to report rates and severities of radiation‐related toxicities and analyze disease‐control outcomes in patients who have received hypofractionated whole breast radiation (HF) with concurrent trastuzumab with or without pertuzumab. We conducted a retrospective cohort study including women with stage I‐III HER2‐positive breast cancer who received HF at the University of Pennsylvania between 1/2005 and 5/2018 with concurrent trastuzumab with or without pertuzumab. Fractionation was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Dreyfuss et al reported radiation-related toxicities in 80 patients receiving hypofractionated whole breast radiation with concurrent PT. There was one grade 3 acute toxicity (fatigue) and no grade 3 late toxicities [ 17 ]. More recently, in a large retrospective cohort of 55 patients, the combination of locoregional breast RT with PT resulted as well tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dreyfuss et al reported radiation-related toxicities in 80 patients receiving hypofractionated whole breast radiation with concurrent PT. There was one grade 3 acute toxicity (fatigue) and no grade 3 late toxicities [ 17 ]. More recently, in a large retrospective cohort of 55 patients, the combination of locoregional breast RT with PT resulted as well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…Even if there are some data on the association of RT and PT in other settings such as palliative bone treatment and postoperative BC treatment [ 17 , 18 , 19 ] with a favourable tolerance profile, no literature data is available on the association between PT and brain fSRT.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Indeed, antiHER2 therapy can be administered under RT and has been shown to be safe, although special attention should be given with regard to cardiotoxicity. [28–30]…”
Section: Discussionmentioning
confidence: 99%
“…[27] Indeed, antiHER2 therapy can be administered under RT and has been shown to be safe, although special attention should be given with regard to cardiotoxicity. [28][29][30] Previous studies have shown that high-risk tumors have the greatest benefit from RT. Although there is heterogeneity in TNBC, most of the TNBC have a high risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%